Sagot :
Answer:
- y = 6x + 2
- change it into standard form.
• y = 6x + 2
• 6x + y = -2
Then substitute 0 to x and y
• 6x + y = -2 6x + y = -2
6(0) + y = -2 6x + 0 = -2
Cancel the Zero's.
6(0) + y = -2 6x + 0 = -2
y = -2 6x = -2
Simplify if possible.
6x + 0 = -2
6x/6 = -2/6
[tex]x = - \frac{1}{3} [/tex]
So the x and y intercepts are:
[tex] y - int = (0 \: - 2)[/tex]
[tex]x - int = - (\frac{1}{3} \: 0)[/tex]
- To find the slope refer below:
[tex]slope = \frac{ y_{2} - y_{1}}{x_{2} - x_{1} } [/tex]
[tex]slope = \frac{0 - ( - 2)}{ - \frac {1}{3} - 0 } [/tex]
[tex]slope = \frac{2} { - \frac{1}{3} } [/tex]
[tex]slope = - 6[/tex]
So therefore, the slope is -6 and the y intercept is (0,2).
#CarryOnLearning